PECULIARITIES OF GEOLOGICAL STRUCTURE AND PHOSPHORITE CONTENT OF PALEOGENE SEDIMENTS OF SOUTHERN HISSAR (ON THE EXAMPLE OF THE TUPALANG AREA) - Axmedov, Shovdullo; Usmonov, Kuvonchbek (Innovatsion texnologiyalar, 2024)
Phosphorites are one of the types of raw materials for the production of phosphate fertilizers. Recently, work has sharply intensified in Uzbekistan to create a local raw material base for the production of phosphate fertilizers. The result of the work carried out in the Republic was the identification of large deposits of phosphorites of a new, granular type in the Central Kyzylkum desert. However, the existing raw material base is insufficient for the development of the production of phosphate fertilizers, therefore, further intensification of geological exploration work is required in order to expand reserves of phosphate raw materials. The article presents the features of Paleogene deposits in the South Gissar region and, using the example of the Tupalang area, considers the distribution of phosphite ores. As a result of the study, it was found that phosphorite sandstones in the Tupalang region are suitable for agriculture as an inexpensive local raw material, which helps maintain productivity, increase the yield of cotton, grain and other crops, partially replace mineral fertilizers with good profitability, and the mining conditions of the study area are favorable conditions for open development of phosphorite-containing rocks